Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae) - Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2018)
Based on new topotypical material, the apterous carventine genus Crassocoris Bai, Heiss & Cai, 2007 (Hemiptera: Heteroptera: Aradidae) with the type species C. hsiaoi Bai, Heiss & Cai, 2007, is redescribed. A new, closely related apterous genus and species, Paracrassocoris hekouensis gen. nov., sp. nov. is described from Hainan, China. The diagnostic morphological features of both taxa are described and illustrated.